STAKEHOLDER ANALYSIS OF HEALTH CENTER ACCREDITATION POLICY IN BENGKALIS REGENCY IN 2021 - Agustina Agustina; Kiswanto Kiswanto; Budi Hartono; Zaenal Abidin; Zulfan Sa'am (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
ABSTRACTRegulation of the Minister of Health Number 75 of 2014 concerning Community Health Centers concerning Accreditation states that in order to improve the quality of puskesmas services, it must be accredited periodically at least once every 3 years. with basic accreditation passing, there are 6 health centers, accreditation with intermediate graduation is 9, the main graduation result is 1 health center. This study uses a qualitative method with a Rapid Assessment Procedure (RAP) research design. Primary data collection was carried out by in-depth interviews and observations. Informants are the Secretary of the Health Service, Head of Yankees, Head of Primary and Supporting Health, holder of the accreditation program, the Accreditation Support Team for Puskesmas, BAPEDA, and BPKAD in Bengkalis Regency. as Context Setters are Bappeda and BKAD. The low graduation rate for Puskas accreditation is due to the lack of budget for Puskas accreditation, the distribution of puskesmas human resources and the lack of puskesmas commitment in implementing puskesmas accreditation. For stakeholders involved in the Bengkalis District Health Center Accreditation Policy to prioritize the implementation of the Puskesmas Accreditation Policy to improve the quality of services at the Puskesmas on an ongoing basis starting from the input to the outcome of implementing the Puskesmas accreditation.